A Study of Religious Slaughter From the Perspective of Islamic Jurisprudence - Nasrat, Abdul Naser (Journal of Social Sciences - Kabul University, 2020)
Slaughter, in its literal sense, refers to the beheading of animals. In Islamic jurisprudence, slaughter is one of the prescribed methods of purifying animals, which is achieved by cutting the four veins in the animal's neck. The practice of sacrificial slaughter for the sake of nearness to God dates back to the time of Adam (PBUH), when his two sons, Abel and Cain, offered a ram and wheat as sacrifices, respectively. According to Islamic teachings, the tool used for slaughter must be made of iron, such as a knife. However, if iron tools are unavailable and there is a risk of the animal perishing, slaughtering with a sharp object such as a stone is considered permissible.